2014
DOI: 10.2147/ijnrd.s66390
|View full text |Cite
|
Sign up to set email alerts
|

The deleterious effects of arteriovenous fistula-creation on the cardiovascular system: a longitudinal magnetic resonance imaging study

Abstract: Aim: Arteriovenous fistula-formation remains critical for the provision of hemodialysis in endstage renal failure patients. Its creation results in a significant increase in cardiac output, with resultant alterations in cardiac stroke volume, systemic blood flow, and vascular resistance. The impact of fistula-formation on cardiac and vascular structure and function has not yet been evaluated via "gold standard" imaging techniques in the modern era of end-stage renal failure care. Methods: A total of 24 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…In contrast, AVF creation was associated with significant right ventricle (RV) dilatation and deterioration in RV function. Similar observations were reported in a longitudinal series including 24 ESRD patients [45]. Sequential cardiac magnetic resonance imaging (MRI) showed significant increases in LV and RV end-systolic volumes, left and right atrial area and LV mass following AVF creation.…”
Section: Haemodynamic Impacts Of High-flow Avf In Patients Under Chrosupporting
confidence: 81%
“…In contrast, AVF creation was associated with significant right ventricle (RV) dilatation and deterioration in RV function. Similar observations were reported in a longitudinal series including 24 ESRD patients [45]. Sequential cardiac magnetic resonance imaging (MRI) showed significant increases in LV and RV end-systolic volumes, left and right atrial area and LV mass following AVF creation.…”
Section: Haemodynamic Impacts Of High-flow Avf In Patients Under Chrosupporting
confidence: 81%
“…The increased venous return increases right atrial, pulmonary artery, and LV enddiastolic volumes, causing LV hypertrophy as a result of the increased workload. 1 Increased LV mass is linked to higher cardiovascular morbidity and mortality. 2 Additionally, reduced systemic vascular resistance in AVF-associated HOHF leads to activation of the sympathetic nervous system and renin angiotensin aldosterone system, further inducing pathologic cardiac remodeling.…”
Section: Pathophysiology Of Av Fistula-associated Hohfmentioning
confidence: 99%
“…A prospective magnetic resonance (MR) study among CKD stage 5 patients demonstrated significant increases in LA size, LVEDV, LV mass, and cardiac output at 6 months after fistula creation. 55 However, interpretation of these findings must be tempered by the lack of a control group, which makes it difficult to separate the effect of a progressive decline in kidney function (and subsequent volume overload) from the effect of fistula creation.…”
Section: Hemodynamics Of Fistula Creationmentioning
confidence: 99%
“…Similar to the increase in LV workload, there is an increase in RV systolic performance as well as increased right atrial size and RVEDV. 55 The increase in blood volume as well as the increased RV performance may lead to increased pulmonary flow and possibly increased pulmonary pressure resulting in pulmonary hypertension. There may be a relationship between the degree of pulmonary hypertension and the age and flow rate of the fistula.…”
Section: Hemodynamics Of Fistula Creationmentioning
confidence: 99%